Rola „Przeglądu Bibliotecznego” w upowszechnianiu zagadnień automatyzacji bibliotek w Polsce w latach 1989-2008 - Gruszka, Zbigniew (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The article presents Polish libraries automation since 1989 and the role of “Library Review”, the oldest scientific periodical for librarians in Poland, in popularization of its main directions. The automation was introduced to Polish libraries in mid-sixties, first as an experiment, then as an informational, bibliographical and library tool. After 1989 librarians could compare their experiences with other libraries from abroad and find out about new library trends. The texts published in “Library Review” present opinions about implementations of MARC format, usage the integrated library systems and organization of central catalogue. The necessity of protection the most valuable items caused the interest in digitalization. Finally the on-line services and usefulness of Internet were described. The articles published in “Library Review” show main directions of changes in Polish librarianship for the last years and are a proof that editorial board of “Library Review” has been paying a great attention to the new technologies.